Global research hotspots and trends of iodinated contrast agents in medical imaging: a bibliometric and visualization analysis - Liu, Yun; Dong, Yonghai; Xie, Fei (Frontiers in Medicine, 2024)
Objective This study employs bibliometric methods to explore the global research dynamics of iodine contrast agents in medical imaging. Through the visualization of knowledge maps, it presents research progress and reveals the research directions, hotspots, trends, and frontiers in this field. Methods Using Web of Science Core Collection database, CiteSpace and VOSviewer were employed to conduct a visual analysis of the global application of iodine contrast agents in medical imaging over the past four decades. The analysis focused on annual publication volume, collaboration networks, citation characteristics, and keywords. Results A total of 3,775 studies on the application of iodine contrast agents in medical imaging were included. The earliest paper was published in 1977, with a slight increase in publications from 1991 to 2004, followed by a significant rise after 2005. The United States emerged as the leading country in publication volume. Harvard University was identified as a globally influential institution with 126 publications. Although a large author collaboration cluster and several smaller ones were formed, most collaborations between authors were relatively weak, with no high-density integrated academic network yet established. Pietsch Hubertus was the most prolific author, while Bae KT was the most highly co-cited author. The most highly cited journal was Radiology, with 2,384 citations. Co-occurrence analysis revealed that the top three keywords by frequency were “agent,” “CT,” and “image quality.” Keyword clustering analysis showed that the top three clusters were “gadolinium,” “gold nanoparticles,” and “image quality.” The timeline analysis indicated that clusters such as “gadolinium,” “gold nanoparticles,” “image quality,” and “material decomposition” exhibited strong temporal continuity, while the keyword with the highest burst value was “digital subtraction angiography” (19.38). Burst term trend analysis suggested that recent research has been focusing on areas like “deep learning,” “risk,” “radiation dosage,” and “iodine quantification.” Conclusion This study is the first to systematically reveal the global trends, hotspots, frontiers, and development dynamics of iodine contrast agents in medical imaging through the use of CiteSpace and VOSviewer. It provides a novel perspective for understanding the role of iodine contrast agents in imaging and offers valuable insights for advancing global research in medical imaging.